Identification of types of drop techniques with pulling on Pencak Silat Matches Regulation in 2022 / Zulfikar Ubaidillah Riky, Kurniati Rahayuni and Alwi Idrus - Ubaidillah Riky, Zulfikar; Rahayuni, Kurniati; Idrus, Alwi (2024)
Changes to the pencak silat regulations in 2022 regarding technical playing in the sparring category pencak silat athletes have an impact on the emergence of new types of fall techniques. But until now, there has been no scientific evaluation or discussion of the types of fall techniques with the pull that have been used. Therefore, this research aims to analyze the types of fall techniques with pulls in the sparring category pencak silat athletes as the first step of evaluating and learning techniques in depth. This research method uses a visual research method with qualitative and quantitative data analysis techniques. The number of subjects identified was 354 videos of matches in 2023 with details, 155 videos from provincial championships, 161 videos from national championships, and 38 from international championships. The research findings are eleven types of fall techniques with pulls described qualitatively. From the results of quantitative data, it is known that three types of techniques are often used in provincial, national, and international matches, including type 6 – pull, catch, and sweep (25.61%), type 3 – pull and cutout (19.35%), and type 5 – pull and side fall hook (18.77%).